The Relevance of Collaborative Learning in the Perspective of Lev Vygotsky's Social Constructivism: A Literature Review - Wasiatul Maghfiroh; Ahmad Ihwanul Muttaqin (Journal of Islamic Education Research, 2025)
This study aims to analyze the relevance of collaborative learning within the theoretical framework of Lev Vygotsky’s social constructivism, particularly by examining how the concepts of the Zone of Proximal Development (ZPD) and scaffolding are operationalized in collaborative practices. Although collaborative learning has been widely implemented in contemporary classrooms, limited literature explicitly integrates it with Vygotskian constructs in a comprehensive theoretical review. This research employed a qualitative library research design using a systematic literature review approach. Academic sources published between 2015 and 2025 were identified through major databases, screened using inclusion and exclusion criteria, and analyzed thematically following PRISMA procedures. The analysis focused on four dominant themes: collaboration as a mechanism of ZPD, layered scaffolding (cognitive, metacognitive, and socio-emotional), socio-emotional dynamics in group interaction, and digital collaborative learning in relation to 21st-century skills. The findings indicate that collaborative learning functions as the practical operationalization of ZPD through peer interaction and shared meaning-making. Scaffolding is most effective when distributed across teachers, peers, and digital agents. Socio-emotional factors, such as trust and conflict regulation, serve as active mechanisms supporting cognitive internalization. The novelty of this study lies in proposing the concept of group-ZPD and integrating multi-modal scaffolding, socio-emotional learning, and digital mediation into a unified Vygotskian framework. This study contributes theoretically by extending social constructivism into digital contexts and practically by offering design principles for collaborative learning aligned with 21st-century competencies.